Effects of elevated atmospheric CO(2) concentrations, clipping regimen and differential day/night atmospheric warming on tissue nitrogen concentrations of a perennial pasture grass - Volder, Astrid (AoB Plants, 2015)
Forecasting the effects of climate change on nitrogen (N) cycling in pastures requires an understanding of changes in tissue N. We examined the effects of elevated atmospheric CO(2) concentration, atmospheric warming and simulated grazing (clipping frequency) on aboveground and belowground tissue N concentrations and C : N ratios of a C3 pasture grass. Phalaris aquatica L. cv. ‘Holdfast’ was grown in the field in six transparent temperature gradient tunnels (18 × 1.5 × 1.5 m each), three at ambient atmospheric CO(2) and three at 759 p.p.m. CO(2). Within each tunnel, there were three air temperature treatments: ambient control, +2.2/+4.0 °C above ambient day/night warming and +3.0 °C continuous warming. A frequent and an infrequent clipping treatment were applied to each warming × CO(2) combination. Green leaf N concentrations were decreased by elevated CO(2) and increased by more frequent clipping. Both warming treatments increased leaf N concentrations under ambient CO(2) concentrations, but did not significantly alter leaf N concentrations under elevated CO(2) concentrations. Nitrogen resorption from leaves was decreased under elevated CO(2) conditions as well as by more frequent clipping. Fine root N concentrations decreased strongly with increasing soil depth and were further decreased at the 10–60 cm soil depths by elevated CO(2) concentrations. The interaction between the CO(2) and warming treatments showed that leaf N concentration was affected in a non-additive manner. Changes in leaf C : N ratios were driven by changes in N concentration. Overall, the effects of CO(2), warming and clipping treatments on aboveground tissue N concentrations were much greater than on belowground tissue.